Optimization parameters to reduce the warpage defect of plastic injection molding process for a thin-shell part using design of experiment - Radhwan, H.; Nasir, S. M.; Mohd Rashidi, Maarof; Kamarudin, K.; Abdellah, Abdellah el-hadj (IOP Publishing, 2019)
Development of light, small and thin plastic products that possess high strength characteristic such as electronic devices have become one of the tremendous demands in the plastic injection molding industry nowadays. However, smaller and thinner wall part design has increased the possibility for the parts to warp. The aim of this study is therefore to determine the best set combination of molding parameters that could reduce the warpage defect. There are six parameters that have been selected in this study which are mold temperature, melt temperature, packing time, cooling time, injection time and packing pressure. Taguchi orthogonal array is used to simplify the experimental runs. The analysis is done by applying S/N ratio approach and ANOVA method. Based on the results obtained from the analysis, it is found that the best set combination parameters give out the smallest warpage value.